Kekuatan Sertifikat Hak Milik Sebagai Jaminan Kredit di BRI Unit Halilulik Desa Naitumu Kecamatan Tasifeto Barat Kabupaten Belu - Bone Lau, Hildegard Blinda Lestari; Nubatonis, Orpa J; Dju Bire, Chatryen M (Artemis Law Journal, 2024)
This study aims to find out and analyze the strength of title certificates as bank credit guarantees carried out in the BRI Halilulik unit, Naitimu Village, West Tasifeto District, Belu Regency. The research method used in this writing is empirical research. The data collection of this research uses literature studies, document studies, observations and interviews. The results of this study show that (1) the strength of the title certificate used as collateral in credit granting transactions in the halilulik bri unit has the highest category that has a strong potential to get credit from the Bank as a creditor because in terms of security for the lender or the Bank, title is certainly the main choice and is a fairly strong type of right. (2) factors that cause a customer to lose a certificate of ownership as collateral in the provision of credit at the bri halilulik unit which include internal factors and external factors as the cause of the customer losing the certificate of ownership.